Case report: Cerebrotendinous xanthomatosis with a novel mutation in the CYP27A1 gene mimicking behavioral variant frontotemporal dementia - Chun, Min Young; Heo, Nam Jin; Seo, Sang Won; Jang, Hyemin; Suh, Yeon-Lim; Jang, Ja-Hyun; Kim, Young-Eun; Kim, Eun-Joo; Moon, So Young; Jung, Na-Yeon; Lee, Sun Min; Kim, Hee Jin (Frontiers in Neurology, 2023)
Background Cerebrotendinous xanthomatosis (CTX) is a rare autosomal recessive lipid storage disease caused by a mutation in the CYP27A1 gene. Due to the disruption of bile acid synthesis leading to cholesterol and cholestanol accumulation, CTX manifests as premature cataracts, chronic diarrhea, and intellectual disability in childhood and adolescence. This report presents a case of CTX with an unusual phenotype of behavioral variant frontotemporal dementia (bvFTD) in middle age. Case presentation A 60-year-old woman presented with behavioral and personality changes. She showed disinhibition, such as hoarding and becoming aggressive over trifles; compulsive behavior, such as closing doors; apathy; and dietary change. The patient showed a progressive cognitive decline and relatively sparing memory and visuospatial function. She had hyperlipidemia but no family history of neurodegenerative disorders. Initial fluid-attenuated inversion recovery (FLAIR) images showed a high signal in the periventricular area, and brain spectroscopy showed hypoperfusion in the frontal and temporal lobes, mimicking bvFTD. However, on physical examination, xanthomas were found on both the dorsum of the hands and the Achilles tendons. Hyperactive deep tendon reflexes in the bilateral biceps, brachioradialis, and knee and positive Chaddock signs on both sides were observed. Four years later, FLAIR images showed symmetrical high signals in the bilateral dentate nuclei of the cerebellum. Her serum cholestanol (12.4 mg/L; normal value ≤6.0) and 7α,12α-dihydroxycholest-4-en-3-one (0.485 nmol/mL; normal value ≤0.100) levels were elevated. A novel likely pathogenic variant (c.1001T>A, p.Met334Lys) and a known pathogenic variant (c.1420C>T, p.Arg474Trp) of the CYP27A1 gene were found in trans-location. The patient was diagnosed with CTX and prescribed chenodeoxycholic acid (750 mg/day). Conclusions This report discusses the case of a middle-aged CTX patient with an unusual phenotype of bvFTD. A novel likely pathogenic variant (c.1001T>A, p.Met334Lys) was identified in the CYP27A1 gene. Early diagnosis is important because supplying chenodeoxycholic acid can prevent CTX progression.